Faktor – Faktor Yang Mempengaruhi Kinerja UMKM di Kabupaten Purworejo - Zidni Husnia Fachrunnisa; Mustaghfiroh; Anandita Zulia Putri (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the effect of personality, human resource competence, use of accounting information, and venture capital on the performance of MSMEs. The population of this study is the owner of MSMEs in Purworejo Regency. The sampling method used is purposive sampling technique. The sample was taken as many as 176 MSMEs in Purworejo Regency. Collecting research data using a questionnaire method distributed online. Data processing using SPSS Statistic version 26 application. Data were analyzed using multiple linear regression analysis. The results showed that personality, human resource competence, use of accounting information, and business capital had a positive influence on the performance of MSMEs. The better the personality and competence of human resources, as well as the use of accounting information will improve the performance of SMEs. In addition, the greater the amount of business capital can also improve the performance of MSMEs.